2021
DOI: 10.1002/hyp.14294
|View full text |Cite
|
Sign up to set email alerts
|

Canopy structure metrics governing stemflow funnelling differ between leafed and leafless states: Insights from a large‐scale rainfall simulator

Abstract: An increasing number of studies have examined the effects of various biotic and abiotic factors on stemflow production. Of those that have ascribed the importance of canopy structure to stemflow production, there has been a bias towards field studies.Coupling Bayesian inference with the NIED (National Research Institute for Earth Science and Disaster Resilience, Tsukuba, Japan) large-scale rainfall simulator, this study leveraged a unique opportunity to control rainfall amounts and intensities to pinpoint the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 72 publications
0
7
0
Order By: Relevance
“…Iida et al. (2021) found inconsistent relationships between stemflow production and foliation as well. At present, variation in pour point fluxes for a constant rainfall intensity cannot be simply predicted as a linear function of foliation and branch angle.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Iida et al. (2021) found inconsistent relationships between stemflow production and foliation as well. At present, variation in pour point fluxes for a constant rainfall intensity cannot be simply predicted as a linear function of foliation and branch angle.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the rainfall simulation experiments indicated that pour point fluxes could vary with the degree of foliation and the branch angle, but did not uncover consistent simple relationships between canopy architecture and the pour point flux. Iida et al (2021) found inconsistent relationships between stemflow production and foliation as well. At present, variation in pour point fluxes for a constant rainfall intensity cannot be simply predicted as a linear function of foliation and branch angle.…”
Section: Assessment Of Pour Points In the Banksia Woodlandmentioning
confidence: 99%
See 2 more Smart Citations
“…The positive relation of biomass with stemflow yield and funneling ratio agreed with the reports on Myricaria squamosa (Zhang et al., 2015), Cryptomeria japonica D. Don, and Chamaecyparis obtuse (Siebold & Zucc.) Endl (Iida et al., 2021). Besides, relative to scattered shrubs, the stronger supporting structure of clumped shrubs (i.e., smaller LLW (2.509 vs. 2.640, unitless)) contributed to their stemflow advantages.…”
Section: Discussionmentioning
confidence: 99%